Mesopancreatic Stromal Clearance Defines Curative Resection of Pancreatic Head Cancer and Can Be Predicted Preoperatively by Radiologic Parameters: A Retrospective Study. Issue 3 (January 2016) - Wellner, Ulrich F.; Krauss, Tobias; Csanadi, Agnes; Lapshyn, Hryhoriy; Bolm, Louisa; Timme, Sylvia; Kulemann, Birte; Hoeppner, Jens; Kuesters, Simon; Seifert, Gabriel; Bausch, Dirk; Schilling, Oliver; et al.
Abstract : Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a strong fibrotic stromal reaction and diffuse growth pattern. Peritumoral fibrosis is often evident during surgery but only distinguishable from tumor by microscopic examination. The aim of this study was to investigate the role of clearance of fibrotic stromal reaction at the mesopancreatic resection margin as a criterion for radical resection and preoperative assessment of resectability. Mesopancreatic stromal clearance status (S-status) was defined as the presence or absence (S+/S0) of fibrotic stromal reaction at the mesopancreatic resection margin. Detailed retrospective clinicopathologic re-evaluation of margin status and preoperative cross-sectional imaging was performed in a cohort of 91 patients operated for pancreatic head PDAC from 2001 to 2011. Conventional margin positive resection (R+, tumor cells directly at the margin) was found in 36%. However, S-status further divided the margin negative (R0) group into patients with median survival of 14 months versus 31 months (S+ versus S0, P  = 0.005). Overall rate of S+ was 53%. S-status and lymph node ratio constituted the only independent predictors of survival. Stranding of the superior mesenteric artery fat sheath was the only independent radiologic predictor of S+ resection, and achieved a 71% correct prediction of S-status. Mesopancreatic stromal clearance is a major determinant of curative resection in PDAC, and preoperative prediction by cross-sectional imaging is possible, setting the basis for a new definition of borderline resectability. Abstract : Supplemental Digital Content is available in the text